2000
DOI: 10.1523/jneurosci.20-17-06734.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Amplification of Synaptic Input in the Dendrites of Spinal Motoneurons In Vivo

Abstract: The impact of neuromodulators on active dendritic conductances was investigated by the use of intracellular recording techniques in spinal motoneurons in the adult cat. The well known lack of voltage control of dendritic regions during voltage clamp applied at the soma was used to estimate dendritic amplification of a steady monosynaptic input generated by muscle spindle Ia afferents. In preparations deeply anesthetized with pentobarbital, Ia current either decreased with depolarization or underwent a modest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
293
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(314 citation statements)
references
References 47 publications
18
293
0
Order By: Relevance
“…Serotonergic (5-HT) neurons of the raphe nucleus and noradrenergic (NE) neurons from the locus coeruleus may contribute much of this basal excitatory input. 19,20 5-HT and NE act on spinal motor neurons yielding plateau potentials, which may amplify excitatory inputs including reflex inputs. [21][22][23] Plateau potentials originate on dendrites and amplify excitatory inputs up to six-fold, thus leading to sustained firing with minimal excitatory input.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Serotonergic (5-HT) neurons of the raphe nucleus and noradrenergic (NE) neurons from the locus coeruleus may contribute much of this basal excitatory input. 19,20 5-HT and NE act on spinal motor neurons yielding plateau potentials, which may amplify excitatory inputs including reflex inputs. [21][22][23] Plateau potentials originate on dendrites and amplify excitatory inputs up to six-fold, thus leading to sustained firing with minimal excitatory input.…”
Section: Historical Perspectivementioning
confidence: 99%
“…To the extent that these inputs were independent of, or significantly nonlinear functions of cortical activity, their effects on muscle activation would be difficult to predict. Furthermore, plateau potentials mediated by persistent inward calcium channels may actually contribute significantly more net current than the synaptic inputs that trigger them (Lee and Heckman 2000). It has been suggested that they may function as a powerful nonlinear amplifier of synaptic input.…”
Section: Factors Affecting Prediction Accuracymentioning
confidence: 99%
“…Many studies suggest that plateau potentials are recruited under physiological conditions (Eken and Kiehn, 1989;Kiehn and Eken, 1997;Gorassini et al, 1999;Alaburda and Hounsgaard, 2003;Perrier and Tresch, 2005). They may contribute to behaviors by amplifying synaptic inputs to motoneurons (Conway et al, 1988;Hultborn, 1999;Lee and Heckman, 2000) or by specifying the temporal details of motor output (Perrier and Tresch, 2005).…”
Section: Introductionmentioning
confidence: 99%